Treatment Planning of Intensity Modulated Radiation Therapy (IMRT/VMAT): study aid - Sukhikh E. S. Evgeniya Sergeevna; Sutygina Y. N. Yana Nikolaevna; Stakhova O. M. Olga Mikhailovna; Sagov I. R. Islam Ruslanovich (Tomsk, TPU Publishing House, 2024)
Текст на английском языке